X-ray diffraction: a powerful method of characterizing nanomaterials - Sharma, Ravi; Bisen, D P; Shukla, Usha; Sharma, B G (Recent Research in Science and Technology, 2012)
X-ray diffraction techniques are a very useful characterization tool to study, non-destructively, the crystallographic structure, chemical composition and physical properties of materials and thin films. It can also be used to measure various structural properties of these crystalline phases such as strain, grain size, phase composition, and defect structure. XRD is also used to determine the thickness of thin films, as well as the atomic arrangements in amorphous materials such as polymers. This paper reports the importance of X-ray diffraction technique for the characterization of nanomaterials.